PENGARUH KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN KEPEMUDAAN DAN OLAH RAGA KABUPATEN BADUNG - Gusti Ayu Kade Anggita Lestar; Ni Luh Sili Antari (Universitas Triatma Mulya, 2022)
This study aims to determine the effect of communication and work discipline on employee performance and the influence of communication and work discipline on employee performance at Dinas Pendidikan Kepemudaan dan Olah Raga in Badung Regency. In this study using a sample of 86 employees, the sampling technique was to take all civil servants in the field in order to get accurate results for research purposes. The data analysis technique used in this research is multiple linear regression analysis technique. The results showed that communication had a positive and significant effect on employee performance at Dinas Pendidikan Kepemudaan dan Olah Raga in Badung with a value of 19.7%. Work discipline has a positive and significant effect on employee performance with a value of 50.4%. The magnitude of the influence of communication and work discipline on the performance of employees at Dinas Pendidikan Kepemudaan dan Olah Raga in Badung is 19.3%, while the remaining 80.7% is explained by other variables not examined in this study.